Inner nuclear protein Matrin-3 coordinates cell differentiation by stabilizing chromatin architecture - Hye Ji Cha; Özgün Uyan; Yan Kai; Tianxin Liu; Qian Zhu; Zuzana Tothova; Giovanni A. Botten; Jian Xu; Guo-Cheng Yuan; Job Dekker; Stuart H. Orkin (Nature Communications, 2021)
Interactions between chromatin and nuclear components and whether these interactions affect development is not well understood. Here the authors show inner nuclear protein Matrin-3 (Matr3) loss leads to accelerated erythroid maturation, and that Matr3 is involved in chromosomal structure organization and compartmentalization to negatively regulate cell differentiation.